2020
DOI: 10.1007/s15010-020-01506-4
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzymes of fungal origin as a relevant cause of false positive Aspergillus antigen testing in intensive care unit patients

Abstract: Background Galactomannan antigen (GM) testing is widely used in the diagnosis of invasive aspergillosis (IA). Digestive enzymes play an important role in enzyme substitution therapy in exocrine pancreatic insufficiency. As digestive enzymes of fungal origin like Nortase contain enzymes from Aspergillus, a false-positive result of the test might be possible because of cross-reacting antigens of the cell wall of the producing fungi. We, therefore, asked whether the administration of fungal enzymes is a relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The following are the inclusion criteria: (1) diagnostic criteria for connective tissue diseases refer to CTD diagnostic criteria developed by the American College of Rheumatology [ 11 ] and patients with interstitial lung disease confirmed by high resolution CT (HRCT) examination. (2) Patients aged 18–79 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The following are the inclusion criteria: (1) diagnostic criteria for connective tissue diseases refer to CTD diagnostic criteria developed by the American College of Rheumatology [ 11 ] and patients with interstitial lung disease confirmed by high resolution CT (HRCT) examination. (2) Patients aged 18–79 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The administered capsulated drug, i.e., Nortase® contains a mixture of lipase, amylase, and protease produced by Rhizopus oryzae and A. oryzae. Very recently, a dramatic increase of false-positive GM-results in patients receiving Nortase® was reported with 75% of treated individuals testing positive for GM [10]. A whole range of fungi is employed in the industrial production of intravenous drugs, so that GM contamination has been observed repeatedly: examples also include the β-lactam antibiotics piperacillin and meropenem as well as the antifungal agent caspofungin [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, powder diluted in 20 mL of water was tested and yielded a strongly positive reaction in the GM ELISA (Platelia Aspergillus GM ELISA, Bio-Rad Laboratories, Hercules, CA, USA). Upon this result, amphotericin B was discontinued, as antigenemia was considered to be a result of Nortase® administration [10].…”
Section: Casementioning
confidence: 99%